Knowledge Management di Perguruan Tinggi - Harjanto Prabowo (Bina Nusantara University, 2010)
Conceptually, Knowledge Management is the organization's activities in managing knowledge as an asset, it is necessary that knowledge is properly distributed to the right people and in swift time, until they can interact, share knowledge and apply it in their daily work in order to improve organizational performance. In the study of higher education, in addition to being an element forming a sustainable competitive advantage, knowledge is also the value created by the college to be conveyed to consumers. This research discusses the understanding of knowledge management that is implemented in universities.